Prevalence of coinfections in a cross-sectional cohort of women screened for multiple pathogens in Peru - Pella-Saavedra, Priscilla (2023)
Objective: To determine the prevalence and risk factors of sexually transmitted infections (STIs) including Chlamydia trachomatis, Ureaplasma urealyticum and Mycoplasma genitalium among asymptomatic women with human papillomavirus (HPV) infection. Methods: A cross-sectional study was performed in 842 asymptomatic women from Cajamarca, Peru. The pathogens were detected using polymerase chain reaction (PCR) and the results were analyzed according to the HPV status: high-risk HPV, low-risk HPV and negative for HPV. Demographical and gyneco-obstetric data was analyzed to identify risk factors. Results: We found that 23.99% (202/842) women were positive for HPV, of whom 79.21% (160/202) were infected with a high-risk genotype. Co-infections were evaluated and 14.38% (23/160) were positive for Ureaplasma urealyticum, 9.38% (15/160) for Chlamydia trachomatis and 1.25% (2/160) for Mycoplasma genitalium. We found a significant association between HPV genotype and the number of children, partners, and history of sexual abuse. The co-infection between high-risk HPV and Chlamydia trachomatis was associated with number of abortions, number of sexual partners and no use of condom. Finally, co-infection between high-risk HPV and Ureaplasma urealyticum was associated with no use of condom and history of STIs. Conclusion: HPV infection continues to be a highly relevant problem in Peru, particularly due to the high prevalence of high-risk genotypes. In addition, we report high rates of co-infections with other STIs, such as U. urealyticum and C. trachomatis. We highlight the importance of active surveillance to promptly diagnose these infections, since they may lead to persistent HPV infections.